PERSEPSI GURU PPKN TENTANG PERUBAHAN KURIKULUM 2013 MENUJU KURIKULUM MERDEKA DI MTSN 1 WATAMPONE - Mustaring Mustaring; Muh. Sudirman; Aderiza Cahya Ayu Restina Idrus (Jurnal Tomalebbi, 2024)
Civics Teachers' Perceptions of the 2013 Curriculum Changes Towards an Independent Curriculum at MTs Negeri 1 Watampone. Thesis. Pancasila Citizenship Education Study Program, Department of Law and Citizenship, Faculty of Social and Legal Sciences, Makassar State University. (Supervised by Mustaring and Muh. Sudirman). This research was conducted with the aim of finding out: 1) PPKn Teachers' Knowledge about the 2013 Curriculum Changes Towards an Independent Curriculum at MTs Negeri 1 Watampone, and 2) PPKn Teachers' Readiness regarding the 2013 Curriculum Changes Towards an Independent Curriculum at MTs Negeri 1 Watampone. This type of research is qualitative research using a descriptive approach, therefore, in order to achieve a research objective, data collection techniques are used, namely observation, interviews, documentation. The informants for this research were 3 PPKn teachers. The results show that: 1. PPKn teachers' knowledge about curriculum changes at MTsN 1 Watampone is from several aspects of assessment regarding the concepts and principles of the independent curriculum, it can be seen that the teacher has understood and knows the concepts and principles in the independent curriculum 2. The readiness of PPKn teachers regarding curriculum changes at MTsN 1 Watampone can be categorized as ready, this is proven by fulfilling the assessment aspects, namely having teaching tools, assessment tools, adapting learning methods, as well as attending training or workshops related to the independent curriculum.